Study by next generation sequencing of sudden cardiac death (SCD). Issue 1 (December 2019) - Boschi, Beatrice; Giotti, Irene; Pelo, Elisabetta; Ricci, Ugo
Abstract: Sudden cardiac death (SCD) is one of the most common causes of death; most SCD are related to secondary arrhythmias, to structural heart disease, or to primary electrical abnormalities of the heart. A significant number of SCD, especially among young people, are due to genetic heart disorders, both with structural and arrhythmogenic abnormalities. However SCD occurs also in patients with negative clinical history, autopsy is not always conclusive for a diagnosis. Recent technological advances in DNA sequencing, have led to the commercialization of genetic testing now widely available in clinical practice. In particular, next generation sequencing, allows the large-scale and rapid assessment of entire genomes. Analysis of SCD with a NGS panel of 174 genes was performed in our laboratory in order to identify the genetic causes and thus to direct the clinician to an accurate clinical and genetic screening of relatives. Two SDC were studied: Case 1: female, 57, without story of syncope and no previously highlighted cardiac alteration, died post cardiac arrest; negative family history. Autopsy was apparently negative. Case 2: male, 52, who died during a football game; negative family history, neurological episodes occurred before death was reported by close relative. Autopsy was positive for ventricular hypertrophic. In both cases we made a genetic diagnosis.